Vonoprazan and amoxicillin dual therapy as the first‐line treatment of Helicobacter pylori infection: A systematic review and meta‐analysis - Du, Ren‐Chun; Hu, Yu‐Xin; Ouyang, Yaobin; Ling, Li‐Xiang; Xu, Jing‐Yuan; Sa, Rina; Liu, Xiao‐Shun; Hong, Jun‐Bo; Zhu, Yin; Lu, Nong‐Hua; Hu, Yi (Helicobacter (Cambridge, Mass.), 2024)
Background Recent clinical trials have evaluated the efficacy of vonoprazan‐amoxicillin (VA) dual therapy as the first‐line treatment for Helicobacter pylori infection in different regions with inconsistent results reported. In this systematic review and meta‐analysis, we aimed to evaluate the efficacy of VA dual therapy compared to the currently recommended therapy for eradicating H. pylori. Materials and Methods A comprehensive search of the PubMed, Cochrane, and Embase databases was performed using the following search terms: (“Helicobacter” OR “H. pylori” OR “Hp”) AND (“vonoprazan” OR “potassium‐competitive acid blocker” OR “P‐CAB”) AND (“amoxicillin” OR “penicillin”) AND (“dual”). The primary outcome was to evaluate the eradication rate according to intention‐to‐treat and per‐protocol analysis. The secondary outcomes were adverse events and compliance. Results A total of 15 studies involving 4, 568 patients were included. The pooled eradication rate of VA dual therapy was 85.0% and 90.0% by intention‐to‐treat and per‐protocol analysis, respectively. The adverse events rate and compliance of VA dual therapy were 17.5% and 96%, respectively. The efficacy of VA dual therapy was superior to proton pump inhibitors‐based triple therapy (82.0% vs. 71.4%, p < 0.01) but lower than vonoprazan‐containing quadruple therapy (83.1% vs. 93.3%, p = 0.02). 7‐day VA dual therapy showed lower eradication rates than 10‐day (χ2 = 24.09, p < 0.01) and 14‐day VA dual therapy (χ2 = 11.87, p < 0.01). The adverse events rate of VA dual therapy was lower than vonoprazan triple therapy (24.6% vs. 30.9%, p = 0.01) and bismuth‐containing quadruple therapy (20.5% vs. 47.9%, p < 0.01). No significant difference of compliance was observed between VA dual therapy and each subgroup. Conclusion VA dual therapy, a novel regimen, showed high efficacy as the first‐line treatment for H. pylori eradication, which should be optimized before application in different regions.